Implementing a purpose model of status-functions through ontologies to support the social reasoning of agents - Cunha, Rafhael R.; Hübner, Jomi F.; Brito, Maiquel de (Anais do Workshop-Escola de Sistemas de Agentes, seus Ambientes e Aplicações (WESAAC), 2021)
In multi-agent systems (MAS), the agents may have goals that depend on others and on shared interpretation about the facts that occur in the system. These goals are thus social goals. Artificial institutions provide such a social interpretation by assigning statuses to the concrete elements that compose the system. These statuses enable the assignee element to perform functions that are not exclusively inherent to their design features. However, the enabled functions are not explicit in the existing models of artificial institutions. This limits the agents in reasoning to achieve their social goals in institutional contexts. Considering this problem, this paper proposes a model based on ontologies to express the functions associated with status-functions. We illustrate the model through some examples implemented in the JaCaMo framework, highlighting the benefits that agents acquire when using purposes for reasoning about the satisfaction of their social goals.